PELATIHAN MAPLE 18 SEBAGAI BENTUK IMPLEMENTASI TEKNOLOGI PEMBELAJARAN PADA MATERI TURUNAN MAHASISWA PENDIDIKAN MATEMATIKA - Istiani, Ana; Permata Sari, Reni; Febriyanti, Niken; Fathur Ardien Arzacky, Miftah; Puspita Sari, Intan (ABDI AKOMMEDIA : JURNAL PENGABDIAN MASYARAKAT, 2024)
The need for learning innovation using technology is urgently needed. One of them is in the world of education. This service activity aims to provide training on the use of Maple 18 software as a technology to support learning for Mathematics Education students at the Muhammadiyah University of Pringsewu Lampung with a focus on the use of Maple 18 software in derivative material. The method used in this service is the lecture method followed by the discussion and question and answer method, followed by the simulation method and direct practice and evaluation method. This service activity has work stages, starting with the preparation, implementation and evaluation stages to determine whether the service activity meets the target, namely increasing learning experiences related to the use of Maple 18 software as supporting technology in learning.